1995
DOI: 10.1017/s0022215100129172
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic fenestration of choanal atresia

Abstract: We report two cases of unilateral choanal atresia and one of choanal stenosis treated successfully by endoscopic fenestration, with no recurrence at a mean follow-up of 18 months. Rigid endoscopy and axial CT scanning confirm the clinical diagnosis and this technique avoids the need for stenting or prolonged postoperative stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…Since the first description of choanal atresia in 1755 [7], multiple surgical techniques have been proposed to repair the malformation [2,8], these surgical procedures can be divided into four main approaches: transantral, transpalatal, trans-septal and transnasal [9,10]. Today, the transnasal endoscopic method is the most widely accepted repair technique [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first description of choanal atresia in 1755 [7], multiple surgical techniques have been proposed to repair the malformation [2,8], these surgical procedures can be divided into four main approaches: transantral, transpalatal, trans-septal and transnasal [9,10]. Today, the transnasal endoscopic method is the most widely accepted repair technique [8].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical presentation varies from acute airway obstruction to chronic recurrent sinusitis depending on whether CA is unilateral, bilateral, congenital choana atresia occurs in 1/1000-1/8000 births of these cases 45% bilateral 6 .…”
Section: Discussionmentioning
confidence: 99%
“…by Stankiewicz, [4] followed by EL-Guindy et al, Persisting bucconasal or bucopharyngeal membrane are Kamel [16] and Cumberworth et al [7] This technique allows possible causes. [4] And reports have indicated that 90% excellent visualization.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the soft nature of the bone [15] component. [5][6][7] need for intubation before operation. Concerning clinical symptoms, CCA can be diagnosed in several ways; the simplest way is failure to pass a catheter through the nose into the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%